The dialogue with of Ecclesiastes in Paul Fleming’s poetry - Sinilo, Galina V. (Journal of the Belarusian State University. Philology, 2019)
This research paper investigates the reception of The Book of Ecclesiastes in the poetry of Paul Fleming (1609–1640), one of the most significant poets of German Baroque. We show that Fleming obviously represents the main topics and stylistic features of – first of all the aspiration for researching paradoxes and antinomies of objective reality and consciousness, contrasting junction of tragedy and hedonism, pessimism and faith in firmness of human spirit. The important component of artistic world of the German poet is his dialogue with the Bible, especially with The Book of Psalms and The Book of Ecclesiastes. As well as Ecclesiastes, Paul Fleming tries to find the purpose of life in the face of its evident senselessness and acquires it in an honest livelihood, friendship, love, faithfulness to God and to his own. The spirit of moral duty and faith in spite of obvious absurdity of the world unites the biblical sage and the German poet. We prove that the text of The Book of Ecclesiastes is present in Fleming’s texts implicitly, by the means of allusions, which are introduced by indicative words-concepts. First of all, these are such words as eitel and Eitelkeit, including the same range of meanings as the general concept of The Book of Ecclesiastes – häḇäl, ‘all that vanishes’, ‘breath’, ‘frailty’, ‘vanity’, ‘fruitlessness’, ‘futility’, ‘absurdity’. The main concepts of Fleming’s poetry, as well as in The Book of Ecclesiastes, are also man, God, time and eternity. We assert that The Book of Ecclesiastes is one of the most important archetexts of P. Fleming’s poetry – meaning- and text-generating texts. In the dialogue with this text the poet develops his artistic world.
Keywords: German poetry of Baroque; poetry of Paul Fleming; The Bible; The Book of Ecclesiastes; dialogue of texts; archetext; allusion; concept